Uranium levels in the diet of São Paulo City residents - Garcia, F.; Barioni, A.; Arruda-Neto, JDT; Deppman, A.; Milian, F.; Mesa, J.; Rodriguez, O. (Elsevier B.V., 2006)
Natural levels of uranium in the diet of São Paulo City residents were studied, and radionuclide concentrations were measured by the fission track method on samples of typical adult food items. This information was used to evaluate the daily intake of uranium in individuals living in São Paulo City which is, according to our findings, around 0.97 mu g U/day. Using the ICRP Uranium-model, we estimated the uranium accumulation and committed doses in some tissues and organs, as function of time. We compared the output of the ICRP uranium biokinetic model, tailored for the conditions prevailing in São Paulo, with experimental data from other localities. Such comparison was possible by means of a simple method we developed, which allows normalization among experimental results from different regions where distinct values of chronic daily intake are observed. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: uranium in food; uranium uptake; biokinetics